A new endangered species of Mollinedia (Monimiaceae, Laurales) endemic to the Atlantic forest in the state of Espírito Santo, Brazil, supported by morphology and genome size estimation - Pauli, Maria; Peixoto, Ariane Luna; Moraes, Ana Paula; Zavatin, Danilo Alvarenga; Negrão, Raquel; Sano, Paulo Takeo; Lírio, Elton John de (Acta Botânica Brasílica, 2023)
Abstract Mollinedia (Monimiaceae) presents numerous microendemic species, and its centre of diversity is in the Brazilian Atlantic rainforest, where more than half of the species occur. The taxonomy of microendemic species can be challenging because their morphological and genetic variations can be interpreted as a response to geographic isolation rather than a circumscription for different species. In this paper, we describe Mollinedia pignalii Lírio & Pauli, a microendemic species from the Espírito Santo state, Brazil. Vegetatively, M. pignalii is similar to Mollinedia elegans Tul. and Mollinedia schottiana (Spreng.) Perkins; however, it presents the following differences: white-puberulous leaves, staminate flowers with a flat receptacle and 6 to 14 stamens, white-puberulous pistillate flowers with a cupuliform receptacle and 8 to 22 carpels, and white-puberulous drupelets. Due to the similarity between the three species, M. pignalii has been collected and deposited in herbaria under different names. Here, we describe the new species based on morphology and genome size, a comparison with similar species, and ecological comments in an integrative approach. We also provide its conservation status and an identification key for the species of Monimiaceae occurring in the state of Espírito Santo.